Recent patents in absorption cooling systems - Kalogirou, Soteris A. (My University, 2008)
Absorption cooling offers the possibility of using heat to provide cooling. For this purpose heat from a conventional boiler can be used or waste heat and solar energy. When the latter systems are used absorption systems minimize also the adverse effects of burning fossil fuels and thus protect the environment. Absorption systems fall into two major categories, depending on the working fluids. These are the ammonia-water systems, in which ammonia is the refrigerant and lithium bromide-water systems in which water vapor is the refrigerant. This paper initially introduces the two systems and then outlines recent patents in this area. The future trends of research in this area would be on other refrigerant pairs which will be more effective.
Keywords: Absorption systems; Ammonia systems; Lithium bromide systems; Waste heat; Solar energy